IM-sgi – an Interface Model for Shape Grammar Implementations - Tching, J.; Reis, J.; Paio, A. (Artificial Intelligence for Engineering Design, Analysis and Manufacturing, 2019)
Information technologies are a driving force for progress in the design field, allowing new modes of creativity. However, most of the existing computational design tools are focused on the latest stages of the design process and especially directed to drafting operations. Conceptual design tools that support the designer in the creative and inventive early stages of the design project are still in their early development. Shape Grammars (SG) were introduced by George Stiny in the 70’s, allowing the generation of designs according to a set of pre-defined rules. SG computational implementations have the potential to answer the need for tools that can assist designers, architects and artists in the creative process, offering design alternatives, stimulating new ideas and encouraging the search for new design generation processes. Acknowledging this potential, a user-friendly interface seems essential for the adoption of these tools. Taking Scott Chase's interaction model as background, the present investigation is aimed at defining guidelines for the design of graphic-user interfaces of SG inplementations...Inspection methods of Human-computer interaction (HCI) were used to analyse existing SG implementations and understand usability issues. Subsequently, HCI ergonomic criteria for interface evaluation (Bastien & Scapin, 1993) were adapted to establish guidelines for the design of SG implementation interfaces, called IM-sqi. These take into account different user groups, adjustable interaction modes for each user group, and the nature of each task performed by the user.